2017
DOI: 10.1111/inm.12366
|View full text |Cite
|
Sign up to set email alerts
|

Does clinical placement in a community alcohol and other drugs rehabilitation centre influence students’ career intention?

Abstract: Due to an ageing workforce, there is a growing need for greater numbers of nurses to work in areas, such as mental health and alcohol and other drugs (AOD) rehabilitation. These practitioners need to approach their work as 'recovery-oriented practitioners'. Positive experiences and preceptorship during clinical placement in AOD rehabilitation settings might influence students' later career choices and address some of the workforce shortage issues. The aim of the present concurrent, mixed-methods study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…It has been reported that healthcare student's positions and beliefs about alcohol are still unclear and probably stereotyped [85]. Furthermore, specific clinical placements in alcohol rehab facilities were proved effective in sensitizing students about alcohol abuse disorder [86].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that healthcare student's positions and beliefs about alcohol are still unclear and probably stereotyped [85]. Furthermore, specific clinical placements in alcohol rehab facilities were proved effective in sensitizing students about alcohol abuse disorder [86].…”
Section: Discussionmentioning
confidence: 99%
“…Almost thirty years after moving out of the hospital-based training model, nursing education has been firmly established in the tertiary sector internationally (Halcomb & Newton, 2017). Graduates' career choices and their confidence and preparedness to work in a particular setting are impacted upon by a number of factors, including curricula (McCann, Clark, & Lu, 2010), school and workplace cultures, and perspectives projected by lecturers and clinical instructors (McCann, Clark, & Lu, 2010), personal and placement experiences (Che, Chong, & Hairi, 2018;Salamonson et al, 2018;Wareing et al, 2018) and preconceived ideas of settings (Ong et al, 2017;Thongpriwan et al, 2015). Whilst there has been research undertaken examining the preparedness of undergraduate nursing students in some specific clinical areas, such as aged care (Algoso, 2015), critical care and mental health (Ramluggun, Anjoyeb, & D'Cruz, 2017;Thongpriwan et al, 2015), PHC has received far less attention (Keleher, Parker, & Francis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2018; Salamonson et al . 2018). Pereira et al (2018) explored perceptions and knowledge of undergraduate students on identifying and providing interventions to people who smoked cocaine, drawing a quantitative survey sample ( n = 164) from two Brazilian nursing schools.…”
Section: Resultsmentioning
confidence: 99%
“…Salamonson et al . (2018) used a mixed‐methods design to determine perceptions and knowledge of participants ( n = 55) after a clinical placement in a community‐based AOD treatment setting, using both a survey of validated measures of attitudes to AOD recovery and treatment and semi‐structured interviews. Although Salamonson et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation